Respuesta :

Answer:

B) 65

Step-by-step explanation:

Plug in the corresponding numbers to the corresponding variables:

w = -4 ; v = 5 ; u = 2

4w² - v + 3u

4(-4²) - (5) + 3(2)

Remember to follow PEMDAS.

PEMDAS =

Parenthesis

Exponents

Multiplications

Division

Addition

Subtraction

& is the order of operation.

First, solve the power:

4(-4²) - (5) + 3(2)

(-4²) = (-4)(-4) = 16

Next, multiply:

4(16) - 5 + 3(2)

64 - 5 + 6

Finally, combine the terms:

(64 + 6) - 5

70 - 5

65

B) 65 is your answer.

~